Respuesta de variables biomédicas en un test de resistencia a la fuerza explosiva en luchadores - Nicot Balón, R. G.; Ríos Hernández, A. N.; Fara Diallo, M. (Revista Cubana de medicina del deporte y la cultura fisica, 2021)
Introduction: The sport of Wrestling requires, of the technical domain, the development of different motor capacities, including speed, strength and resistance and in particular the combination of these capacities such as explosive strength resistance. In Cuba, in the sport of male wrestling with a test, developed by Ríos Hernández, where the development or degree of adaptation is explored by the training of explosive force resistance. Objective: The purpose of this study was to establish the behavior of biomedical and pedagogical variables through a test of explosive force resistance in two moments of training. Materials and Methods: Retrospective longitudinal research was carried out. The sample was 10 elites athletes who performed circuit test with weights, of 10 stations that simulate some movements, time and pause of combat, at the beginning and end of the general preparation. Blood lactate, heart rate and recovery was studied as well as the number of actions performed. Result: Increased shares, heart rate and lactate were found in the second stage of study as well as poor recovery of these variables in some divisions. The Wrestling Circuit Test is useful as a diagnostic of capacity development. Conclusion: The biomedical and pedagogical variables studied in the Hernández river circuit test and implemented in the wrestling, indisputably expose the physiological changes for the specific work of a combat.